2020
DOI: 10.3390/diagnostics10121025
|View full text |Cite
|
Sign up to set email alerts
|

The Use of the Central Vein Sign in the Diagnosis of Multiple Sclerosis: A Systematic Review and Meta-analysis

Abstract: Background: The central vein sign (CVS) is a radiological feature proposed as a multiple sclerosis (MS) imaging biomarker able to accurately differentiate MS from other white matter diseases of the central nervous system. In this work, we evaluated the pooled proportion of the CVS in brain MS lesions and to estimate the diagnostic performance of CVS to perform a diagnosis of MS and propose an optimal cut-off value. Methods: A systematic search was performed on publicly available databases (PUBMED/MEDLINE and W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
52
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 67 publications
5
52
0
2
Order By: Relevance
“…Based on a meta-analysis evaluating 35 studies, the 40% positive CVS criterion appears to be the optimal threshold to discriminate MS from its mimickers. 18,24 However, integration of the CVS into clinical practice still requires the adoption of standardized criteria that would have to be tested in longitudinal multicentric studies. CVS use is first limited by the additional SWI scanning time (roughly five minutes) that should be included in the already long MRI MS protocol.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on a meta-analysis evaluating 35 studies, the 40% positive CVS criterion appears to be the optimal threshold to discriminate MS from its mimickers. 18,24 However, integration of the CVS into clinical practice still requires the adoption of standardized criteria that would have to be tested in longitudinal multicentric studies. CVS use is first limited by the additional SWI scanning time (roughly five minutes) that should be included in the already long MRI MS protocol.…”
Section: Discussionmentioning
confidence: 99%
“…However, the meta-analysis of Castellaro et al demonstrated that the use of FLAIR* showed no significant differences in the pooled proportion of CVS presence. 24 It is also important to note the high value of 3D high-resolution echo-planar imaging (EPI). 25 Indeed, when compared with other susceptibility images, these optimized 3D-T2* images achieved the best performance in differentiating MS from mimicking disorders.…”
Section: Mri S Equen Ce S For Centr Al Vein S I G N De Tec Ti Onmentioning
confidence: 99%
See 1 more Smart Citation
“… 9 , 10 The CVS has been proposed as a radiologic biomarker and is seen with high frequency in MS lesions, 11 , 12 such that it can effectively differentiate MS from other etiologies associated with nonspecific white matter lesions. 13 , 14 However, whereas the CVS has shown promise in aiding the initial diagnosis of MS based on the evaluation of established lesions, the CVS characteristics of newly appearing T2/FLAIR or Gd+ lesions in MS have not been comprehensively described. In this study, we sought to (1) investigate CVS characteristics of newly developing lesions in MS cases and HCs followed longitudinally; (2) study their relationship with clinical and radiologic measures of disease burden; and (3) describe the frequency of associated DMT changes seen retrospectively in this cohort.…”
mentioning
confidence: 99%
“…7 It has been proposed that having more than 40% lesions with CVS or three or more lesions with CVS is specific for MS. 8 Other studies have proposed varying CVS thresholds and absolute lesion number, with similar degrees of specificity. 7,9 Advanced post-processing techniques, such as T2* and FLAIR* improve discernment of CVS. 10,11,12 In this study we used a gradient echo plural contrast imaging (GEPCI) technique that is based on a multi-echo gradient echo MR sequence and post processing algorithms, to generate images and quantitative maps with different biological contrasts.…”
Section: Introductionmentioning
confidence: 99%